ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA PEGAWAI KANTOR DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA TANJUNGPINANG - Fata Hubbani Ula. TB; Jumiati Sasmita; Susi Hendriani (Jurnal Ekonomi, 2014)
This study focuses on the efforts to analyze the leaderships, work environment and motivation directly or indirectly effect on employee performance at Education and Cultural Office Tanjungpinang. Primary data were collected using questionnaires as tools to prove the result of the study. The subjects were the employees of Education and Cultural Office Tanjungpinang. This study took 102 respondents as samples. This study using path analysis with SPSS tools to prove the result.The result showed that there are direct and indirect positive effects and significant correlation between the variables of leadership and motivated work environment and employee performance. Based on the test result in this study concluded that the better work environment with leadership and work environment with employee motivation, the better employee performance at Education and Cultural Office Tanjungpinang. Based on research, leadership in the Office of Education and the culture needs to be fixed with due regard to participatory behavior and discretionary behavior of a leader. While the factor work environment, employee relations and relations among the tops of the factor needs to be improved and employee motivation, rewards and career development in the form of income other than salary should be increased. Therefore, the role of leadership, work environment, motivation, is crucial to improve the employee performance at Education and Cultural Office Tanjungpinang.